Political Talk and the Triad of Democratic Citizenship - Christian Schnaudt; Rüdiger Schmitt-Beck (Journal of Deliberative Democracy)
Deliberative democracy’s core practice of political discussion is often claimed to entail beneficial ‘self-transformative’ effects on those partaking in it. We examine the assumption that political talk makes for ‘better citizens’ with a special focus on individuals’ orientations toward democracy and their own roles within it. We conceptualize these orientations as a triad of democratic citizenship that encompasses three pillars: (1) the attitudinal dimension of citizens’ support for the democratic political system whose members they are, (2) the normative dimension of views about ‘good’ citizenship, and (3) the behavioral dimension of active participation in this system’s political process. Our analysis offers a comprehensive perspective at how these orientations are affected by engagement and disagreement in political talk across four discursive spheres: (i) informal conversations of a private nature within strong network ties (family and friends), (ii) of a semi-public nature within weak network ties (acquaintances), and (iii) of a public nature outside social networks (strangers), as well as (iv) formalized public discussions at organized events. Drawing on two high-quality surveys from Germany, we find overall positive effects of engagement in informal-private conversations and formalized public discussions on citizenship orientations. The role of semi-public political talk within weak ties appears ambivalent, but its impact is overall rather weak. Strikingly, we observe strong indications that casual conversations with strangers weaken people’s support for the democratic system, participatory norms, and likelihood of active political engagement. Disagreement during political conversations also matters for democratic orientations, and its effects are always positive.